Salman Rushdie and Visual Art and Culture - Mendes, Ana Cristina (2023)
In The Moor’s Last Sigh, Vasco Miranda describes the artist Aurora Zogoiby’s work as an ‘Epico-Mythico-Tragico-Comico-Super-Sexy-High-Masala-Art’ in which the unifying principal was‘Technicolor-Story-Line’ (Salman Rushdie, The Moor’s Last Sigh, 1995). Arguably this seems also like a fitting description for Rushdie’s own form of writing. This chapter considers Rushdie’s visual style of story-telling, by using, for example, ekphrasis. It also highlights the wider context of how his work engages with art and visual culture, for example, the intertextual relationship in The Moor’s Last Sigh between Aurora Zogoiby and the artist, Amrita Sher-Gill. Beyond this, Rushdie has collaborated with artists such as Anish Kapoor and Tom Phillips and engaged with the issues of portraiture. Linking debates around visual representation and celebrity, this chapter explores the wider context between Rushdie’s own forms of writing and their engagement with visual storytelling and visual aesthetics.